PROF. DR DjORDjE JOANNOVIĆ, CORRESPONDING MEMBER OF SERBIAN ROYAL ACADEMY, DEAN, PATHOLOGIST AND FIRST SERBIAN ONCOLOGIST, ONE OF THE WORLD PIONEERS OF THE STUDY OF AUTOAGGRESSION, FOUNDER AND BUILDER OF THE INSTITUTE OF PATHOLOGY, THE MOST TRAGIC PERSONA - Kanjuh, Vladimir (Medicinska istraživanja, 2023)
ORIGIN OF THE FAMILY. BIRTH AND LIFE OF Dj. JOANNOVIĆ IN VIENNA 1-4, 8, 15, 16, 20 1871-1920. The family originates from Metohija. From where she moved to the Banat village of Beodra (today a settlement within Novo Miloševo) and then to Vienna. Father Hariton was a lawyer and senator and managed the estate of the Viennese baron Sina. Mother Marija, maiden name Vlahović. The older brother Simeon was born in 1869. He was engaged in consular affairs. For him Dj. J. was very attached. He lived in Beodra while Dj. J. was in Belgrade. Dj. J. was born on June 16, 1871 in Vienna. Djordje and Simeon were brought up in the spirit of the old Serbian tradition. They were musical: Djordje played the violin and Simeon the piano. Dj. J. did not marry and had no children. He believed that "science is looking for the whole person". Z. Levntal28, internist-cardiologist from Belgrade, author of the statement about Dj.J. in Zagreb’s Yugoslav Medical Encyclopedia, especially researched the social life of Dj.J. It was announced to V.K. that he has reliable evidence that Dj.J. loved women. He lived in one room in his Institute of Pathology. Dj.J. was a "Vienna born boy". In Vienna, he completed primary and secondary school and the Faculty of Medicine. He was promoted to doctor of general medicine on July 1, 1895, at the age of 24. He got a job at the Institute of Pathology of the Faculty of Medicine in Vienna. He became a lecturer in 1896, an assistant professor in 1904, an associate professor in 1910, and a full professor in 1919. At that time, Vienna was one of the centers of world medicine, along with Paris, Berlin, London, Padua, Budapest and St. Petersburg. Dj.J. was at that time the Serb with the highest university title in the world (Fig. 1). Oncology and pathology in Vienna were at a great scientific level. They had the famous pathologist Karl von Rokitansky (1804-1878). He was the bearer of the humoral direction in pathology, in contrast to Rudolf Virchow in Berlin, who advocated cellular pathology. Rokitansky was rector of the University of Vienna and president of the Austrian Academy of Sciences. He performed about 30,000 autopsies17! His student and successor Richard Paltauf (1858 – 1924) was a student of Pasteur and Koch. He was the boss of Dj.J., who collaborated with him from 1895 to 1920. Richard Paltauf, Karl Sternberg and Dj.J. made up the recognized "Vienna School of Experimental Oncology". Dj.J. collaborated with Pick, a student of Paltauf, in his scientific papers. Also, with the famous German pathologist Karl Aschoff. Dj.J. knew the Nobel laureates: Paul Ehrlich40, known for researching humoral immunity and the inventor of Salvarzan and Neosalvarzan, anti-syphilis drugs, and Ilya Ilyich Mechnikov, who discovered phagocytosis. White Russians, by the way, when talking about the results of the reign of their Tsar Nicholas II Romanov, emphasized that during his time Russia had the first two Nobel laureates: Ilya Ilyich Mechnikov in Paris and Ivan Pavlov in St. Petersburg, who discovered conditioned reflexes and dealt with higher nervous activity. After their death, he also wrote obituaries about them. He also greatly appreciated the Serbian academician Vladan Đorđević, wrote about his honorary PhD thesis and his obituary when he died. Dj.J. could have taken over institutes and chairs of pathology in Innsbruck and Prague from Vienna. He even had invitations to come to the USA. Because of his noble patriotism, to help Serbia and the Serbian people, he accepted the invitation to come to Belgrade at the age of 49. Also, he could have succeeded his teacher Paltauf who died in 1925 but did not return from Belgrade to Vienna.